OlofssonM

answers: 1

Register to add an answer

Answer:

Let the present ages of son and father be x and (60 -x) years respectively.

Then, (60 - x) - 6 = 5(x - 6)

=54 - x = 5x - 30

=6x = 84

=x = 14.

=Son's age after 6 years = (x+ 6) = 20 years..

We can also solve by this

Let six years ago son's age be x, and fathers age be 5x.

Then sum of their present age

(x+6)+(5x+6)=60

x+5x+12=60

6x+12=60

6x=60-12

6x=48

x=8

Hence six years ago son's age was 8 years

and present age is 8+6=14 years

Answer=after six years his age will be 14+6=20 years.

279

St-Hilaire

For answers need to register.

83

cents

The time for answering the question is over

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions